Patterns of carbon monoxide poisoning and its association with delayed neuropsychiatric sequela at a tertiary hospital in Riyadh, Saudi Arabia. - Nesrin Alharthy; Aljohara Alanazi; Rakad Alshaibani; Jawaher Albuniyan; Bedour Alharbi; Alreem Almoqaiteeb; Amani Alenazi; Abdullah Alshaibani; Winnie Philip (Saudi Journal of Emergency Medicine)
Background: Carbon Monoxide (CO) is one of the most common environmental causes of acute intoxication globally. It occurs due to impaired tissue oxygenation which has a detrimental impact on systems with high oxygen demands such as cardiovascular and neurological systems. It can lead to Delayed Neuropsychiatric Sequelae (DNS) which may develop in 2-40 days after remission of acute CO poisoning. DNS is defined by recurrent-transient neurological, cognitive, or psychological manifestations. This study was intended to explore the development of DNS for patients exposed to CO intoxication in Saudi Arabia. Methods: A retrospective descriptive cross-sectional study was conducted in subjects who were diagnosed with CO poisoning at King Abdulaziz Medical City (KAMC) and King Abdullah Specialist Children's Hospital (KASCH) in Riyadh during the period from January 2016 to December 2021. Patient demographics, vitals, diagnostic tests, and oxygen therapy at initial presentation were documented. Patient medical records were reviewed at 2-40 days following CO poisoning for development of DNS. The type of developed DNS and the onset time were also documented. Ethical approval was obtained from King Abdullah International Medical Research Center (KAIMARC). Results: A total of 85 patients were diagnosed with CO poisoning and met the study inclusion criteria. Of these, 76% were adults with an average age of 32.36 (SD± 15.20) and 51% were male adults. The majority of the incidents occurred in the winter season (76%), especially in enclosed spaces (84%). 25% of the patients were smokers. Of those 85 patients, only 5 (6%) developed DNS. Common symptoms included dizziness, nausea, and decreased visual acuity in 40% of the cases. The development of DNS manifestations was most likely (80%) to occur at two to ten days after the initial incident. Inferential statistics showed that BMI (p-value = 0.021) and age group (p-value = 0.029) were significantly associated with COHb level, which was not the case for gender and the presence of clinical manifestation. Furthermore, there was no statistically significant association between gender, age, BMI, gender, type of exposure, presence of clinical manifestations, and COHb level with the development of DNS. Only one reported death in this study. Conclusion: The findings of this study showed that few patients who were exposed to CO poisoning have developed DNS. BMI and age group were significantly associated with COHb level. Further larger-scale multicenter studies are needed to assess the factors associated with the development of DNS for patients with CO poisoning. [SJEMed 2023; 4(2.100): S118-S118]